Disparities in the survivorship experience among Latina survivors of breast cancer. Issue 11 (6th April 2018) - Olagunju, Tinuke O.; Liu, Yihang; Liang, Li‐Jung; Stomber, James M.; Griggs, Jennifer J.; Ganz, Patricia A.; Thind, Amardeep; Maly, Rose C.
Abstract : BACKGROUND: The authors investigated disparities in the survivorship experience among Latinas with breast cancer (BC) in comparison with non‐Latinas. METHODS: A cross‐sectional bilingual telephone survey was conducted among 212 Latina and non‐Latina women within 10 to 24 months after a diagnosis of BC (AJCC TNM staging system stage 0‐III) at 2 Los Angeles County public hospitals. Data were collected using the Preparing for Life as a (New) Survivor (PLANS) scale, Perceived Efficacy in Patient‐Physician Interactions Questionnaire (PEPPI), Breast Cancer Prevention Trial (BCPT) Symptom Checklist, Satisfaction with Care and Information Scale, Consumer Assessment of Healthcare Providers and Systems (CAHPS) tool, Charlson Comorbidity Index adapted for patient self‐report, and the 12‐item Short Form Health Survey. Controlling variables included age, stage as determined by the American Joint Committee on Cancer (AJCC) TNM staging system, educational level, and study site in multivariate analyses. RESULTS: The mean ages of Latinas and non‐Latinas were 51.5 years and 56.6 years, respectively. Compared with non‐Latinas, Latinas reported less BC survivorship knowledge (27.3 vs 30.7; P <.0001), were more dissatisfied with BC care information (2.3 vs 3.4; P <.0001), reported lower PEPPI scores (38.2 vs 42.2; P = .03), and experienced more BCPT symptoms (6.4 vs 5.0; P = .04). No differences were noted regarding their confidence in survivorship care preparedness (42.7 vs 41; P = .191), satisfaction with BC survivorship care (9.6 vs 8.8; P = .298), or their discussion with physicians (9.6 vs 8.1; P = .07). These ethnic group differences persisted in multivariate analyses, with the exception of PEPPI. CONCLUSIONS: Latina survivors of BC experienced disparities in BC knowledge and satisfaction with information received, but believed themselves to be prepared for survivorship and were as satisfied with providers, care received, and discussions with physicians as non‐Latinas. Cancer 2018;124:2373‐80 . © 2018 American Cancer Society . Abstract : The authors investigate disparities in the survivorship experience among Latinas with breast cancer in comparison with non‐Latinas. Latina survivors of breast cancer experience disparities in knowledge regarding breast cancer and satisfaction with information received, but believe themselves to be as prepared for survivorship and satisfied with providers, care received, and discussions with physicians as non‐Latinas.